Contribution of the legs to propulsion in frontcrawl swimming - Hollander, A. P.; de Groot, G.; van Ingen Schenau, G. J. (Swimming Science V, 1988)
Because swimming is performed with both arms and legs, the question is often raised, to what extent do the arms or legs contribute to swimming speed? Although it is generally accepted that in front crawl swimming a greater part of the propulsion results from the arm stroke (Adrian, Singh, & Karpovich, 1966; Holmer, 1972), many instructors still spend a lot of time in drilling the leg kick of the crawl stroke, indicating leg kicking's relative importance at least during sprint swimming. Evidence for the contribution of leg action to swimming speed is derived from indirect methods using towing (Counsilman, 1968) or measuring oxygen consumption (Holmer, 1974) or the speed that can be achieved by swimming with arms or legs only (Bucher, 1975; Karpovich, 1935). From these kinds of experiments the power delivered by the arms while swimming arm stroke only cannot be assumed to be the same as when the legs are additionally involved in propelling the body. In the present study, the system to measure active drag (MAD system) (Hollander et al., 1986) was used to study the contribution of the legs to propulsion in front crawl swimming and to discover whether the power delivered by the arms is the same in swimming with and without leg kicking.